Govorljivost in gledališki prevod - Čebulj, Živa (Vestnik za tuje jezike, 2025)
One of the central themes of Theatre Translation Studies is the concept of speakability, which refers to issues such as what gives a dramatic text its performative power, what kind of translation is suitable for the stage, and how to define a translation as speakable. These questions are crucial for understanding the relationship between the written dramatic text and its stage realization, while also opening up space for justifying various translation choices and interventions in the first trans-lation. In this paper, we first discuss the different approaches to the concept of speakability, which are classified into two main groups: the first an intra-textual approach, in which speakability is understood as an intrinsic feature of the dramatic text, while the second argues for an extra-textual, process-oriented approach, in which speakability is the result of the collaboration of various actors in the process. In the empirical part of the article, these theoretical orientations are applied to a specific example: the Finnish play Kokkola by Leea Klemola, translated by Julia Potrč Šavli and staged by the Celje Theatre, directed by Živa Bizovičar, where a translation into the Zasavje dialect was also prepared (Jaša Drnovšek). Based on a few specific examples, we analyse the differences between the original translation, the prompt book, and the stage text (in the premiere performance), as well as how these textual changes occurred. We then examine in more detail the ideological reasons for the use of dialect on stage and compare the reasons for such linguistic choices between the original performance in Finnish (or the Kokkola dialect) and the use of the selected dialect in the Celje performance. The paper concludes with a reflection on how the use of dialect was evaluated in critical responses, and what this means for understanding speakability in contemporary performance practice.
Keywords: dialect; gledališki prevod; govorljivost; narečje; negotiation; performative potency; performativna moč; pogajanje; speakability; Theatre Translation